Green marketing promotion tools and Indian consumers' green purchase intentions. (1st January 2014) - Nath, Vishnu; Agrawal, Rajat; Gautam, Aditya; Sharma, Vinay
The purpose of this study is to examine the relationship of green marketing promotion tools such as environmental advertising and eco-labelling on Indian consumers' intention to purchase a green product. Consumer purchase intentions for green products were considered as a dependent variable, while environmental/green advertising, eco-labelling and consumer skepticism were considered as independent variables. Using a random sample of 545, the multiple regression analysis suggested that green advertising and eco-labelling has significant positive relation to green purchase intentions, while, skepticism towards green marketing promotion tools has no significant affect on green purchase intentions. Based on the results, the study proposes certain courses of action for policy and marketing actors.